The response of glass window systems to blast loadings: An overview. Issue 1 (March 2016) - Zhang, Xihong; Hao, Hong
The failure of glass windows in terrorist bombing attacks and accidental explosion incidents has been cited as one of the major causes to the vast casualties. Many studies have been carried out to investigate the response and vulnerability of glass windows against blast loadings. These include laboratory and field tests that have been carried out to experimentally study glass window performance under explosion scenarios and development of analytical and numerical models to analyze and predict glass window responses. This article reviews literatures on the studies of the response of glass window systems to blast loadings. Over 100 papers and documents that are available in the open literature are reviewed. The background and history of the studies on the topic are also briefed. Understandings about the dynamic material properties of glass and available material models are summarized. Popularly used analysis methods and design standards for monolithic and laminated glass windows are outlined, and their accuracies are discussed. Recent studies including analytical solution, numerical simulation, and experimental investigations on glass window systems are summarized. Mitigation measures for blast-resistant windows are also briefly discussed.